PENGELOLAAN ADMINISTARSI DALAM BIDANG PENGARSIPAN PERKANTORAN BAGI JAJARAN APARAT DESA MANGGIS KECAMATAN MOJOSONGO KABUPATEN BOYOLALI - Siswanto, Dwi Joko; M. Sigit Saksono; Jarwono; Titiek Herawati; Sertar Reynara Gery Nicora; Sertar Ananda Naufal Fadilah (PPM Sdirjianbang Akademi Militer, 2024)
The success of archive management is determined by several factors, including; storage systems, archiving employees, archiving equipment, and of course the work environment. The archive management carried out in Kwarakan Village, Kaloran Subdistrict, Temanggung Regency is very influential on the success or failure in the retrieval of archives. The success in archive management is determined by several factors, including; storage system, archiving staff, archiving equipment, and of course the work environment. The archive management carried out in Kwarakan Village Kaloran Sub district Temanggung Regency is very influential on the success or failure in the retrieval of archives. The goal in organizing PKM, to be able to present information more completely, quickly and correctly, there must be a good work system and procedures in the field of archive management. In the implementation of community service through the method of office archive management training for the Kwarakaan Village Kaloran Sub District Temanggung Regency which organized by the Akmil Defense Management Study Program Lecturer Team, in order to answer one of the problems that appeared, namely that there are still employees who have never received education and training on program so that they do not understand the program that are carried out. Problem solving or providing solutions to the community, the targets achieved The realization of office administration training for Kwarakan Village officials in Kaloran Sub-District, Temanggung Regency in improving office administration management capabilities and skills, training participants totaling 12 people. Then created more harmonious communication and relationships between Akmil personnel and the community of Ds. Kwarakan Kec. Kaloran Kab. Temanggung. Creating TNI-People unity, especially the people of Kwarakan Village, Kaloran District, Temanggung Regency.